THE The Impact Of Covid-19 On The Performance Of The Indonesian Shariah Stock Index (Issi) Stock Portfolio Using The Idx-Ic Sectoral Approach - Iwan Setiawan; Endri; Sigid Eko Pramono (IRTIQO' : Postgraduate Journal of Islamic Economics, Finance and Accounting Studies, 2025)
The development of the capital market has an influence on a country's economic growth, but the Covid-19 pandemic has caused fluctuations in the stock market, especially the sharia stock market in Indonesia. These fluctuations are accompanied by return volatility due to strong pressure in some sectors and rapid growth in other sectors. The aim of this research is to analyze the impact of the Covid-19 incident on the Islamic capital market in Indonesia through an analysis of the formation and evaluation of the performance of an optimal portfolio of Islamic shares using a sectoral approach for one year before and one year during Covid-19. The portfolio formation method uses the Single Index Model (SIM), and performance testing uses the Sharpe Ratio. The secondary data used are weekly closing stock prices and weekly ISSI closing points from March 3, 2019, to February 28, 2022, with the SR011 Retail Sukuk yield as a reference for risk-free asset returns. There was an increase in return performance and the composition of shares that formed an optimal portfolio due to the general response of securities to increasing market performance, which led to positive figures during Covid-19. The portfolio's Sharpe ratio performance always outperformed market performance in both research periods, with the sectors showing the best performance coming from the financial, energy, and technology sectors. Based on the statistical difference test on the Sharpe ratio, it is known that the Covid-19 pandemic has had a significant impact on the Islamic capital market. Investors are advised to be careful in choosing the right sectors during an economic downturn, while authorities are advised to anticipate policies that strengthen vulnerable sectors and prepare sectors that will become the foundation of the economy in times of crisis.